Alteraciones geodinámicas colaterales ocurridas en el barrio 11 de Diciembre del cantón San Vicente en la costa de Manabí debido al sismo de 7.8° en escala Richter del 16 de abril de 2016 - La Mota Dávila, Carlos Julio (2019)
The Natural Risks show the threats and vulnerabilities to which the main towns and villages near the study area are exposed; considering that the telluric movements as such mainly affect the habitable structures, however, the collateral damages that occur in their environment are the aspects that should be paid attention after earthquakes, since it is these that without a good study of impact will affect in the short and medium term periods the communities already installed and those that would come. Why this topic? When we had to participate as rescuers for Guayaquil Firefighters, at the end of operations in Manta, Portoviejo and Bahia, we were assigned to go to Pedernales, so we had to go through San Vicente and stop to eat something to continue towards our destination; It was right there when we talked and listened to the comments of the inhabitants of San Vicente, we were able to observe the hill and see several humble houses settled along the hillside, which we were surprised to see still standing, however, within what we were shared by the inhabitants close to us, a couple of people who lived in one of those houses in question mentioned us that on the other side of the hill (opposite to our point of view) a strong post-earthquake sound would have been heard, at same time as a power outage occurred; It was there when we asked ourselves: "In the near future we will see what really happened here? Why, being in the middle of the affected places, there was not a great visible affectation here?" Six months after the earthquake we returned to San Vicente, we traveled part of the main hillside as civilians, only with the intention of raising some information, finding that they were not only houses, but the community of the neighborhood of December 11 Those who not only live, they also have small areas surrounding their humble houses that they use to cultivate short-cycle plantations for personal consumption and have a few free range animals. When we climbed to the top of the hill, we found a reality that we did not believe in the information we were beginning to collect, but it was true; during our ascent we evidenced several cracks in the terrain that advanced for several meters and presenting different depths and separations between their edges: and as we had suspected in the comments following the earthquake, part of the rear slope had collapsed, showing a large mass of detached earth. Here begins our Case Study, "Collateral Geodynamic Alterations that occurred in the 11th December District of the San Vicente Canton on the Coast of Manabí due to the 7.8 Earthquake on the Richter Scale of April 16, 2016". KEYWORDS Seismology, Post-earthquake, Earthquake, Cracks, Collapse and Geodynamics